An implementation science systematic review of neurophysiological evidence indicates the tinnitus core network as a therapeutic target - Burton-Harris, Lisa Jane; Sanders, Philip Julian; Searchfield, Grant D. (Frontiers in Audiology and Otology, 2023)
Identifying and implementing an effective tinnitus treatment has been a challenge. Despite efforts over many decades, there is no definitive cure for tinnitus yet. Implementation science may assist audiology practitioners and end-user patients in their pursuit of a cure by identifying ways to maximize the use of research findings. Within the context of therapeutic interventions, implementation science is the study of a successful treatment–system fit evidenced by use. Research evidence for tinnitus treatment efficacy is dominated by behavioral questionnaires as they are a pragmatic source of patient-driven data. Neurophysiological evidence of the underlying neural network change correlated with these behavioral findings enhances research conclusions and potential use. This implementation science review systematically sourced and analyzed neurophysiological evidence from 29 studies to find that targeting tinnitus core network neuroplasticity may be the most effective tinnitus treatment. Narrow-band sound treatment has the greatest body of correlated neurophysiological-behavioral evidence. This is the first tinnitus implementation science systematic review. It is hoped that new or improved treatments may emerge from pivoting the evidential lens toward the pragmatic use of neurophysiological evidence. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42022335201.